Pengaruh Sikap Keuangan, Locus of control, Teman Sebaya terhadap Perilaku Pengelolaan Keuangan dengan Literasi Keuangan sebagai Variabel Mediasi - Aida, Nila Nur; Rochmawati, Rochmawati (Jurnal Pendidikan Akuntansi (JPAK), 2022)
The research conducted purpose to analyze the effect of financial attitudes, locus of control, peers on financial management behavior through financial literacy, either directly or indirectly. The population used was 158 students of the 2017 and 2018 Accounting Education Study Program, Faculty of Economics and Business, Surabaya State University. Purposive samples are used in sampling. Collecting data using questionnaires, data processing is carried out with data instrument tests, classical assumptions, regression analysis and path analysis which is processed through the IBM SPSS version 25 application. Getting results, namely: (1) financial attitudes, locus of control, and peers have a direct effect on financial management behavior (2) financial attitudes, locus of control, and peers have an indirect effect on financial literacy (3) Financial literacy has an indirect effect on financial management behavior (4) financial literacy is a mediating variable on financial attitudes, locus of control, and peers with financial management behavior. The advice given is that students are expected to make records of all activities regarding their finances in order to create good financial management behavior.